Ethnomedicinal Plants of the Hamirpur (H.P.) Used for Treatment of the Kidney Stone and Arthritis - Kumar, Amit; Jamwal, Komal (International Journal of Scientific Research in Biological Sciences, 2021)
The extensive survey was conducted in the villages of distt. Hamirpur for the investigation of use of the ethnomedicinal plants. The present study was conducted to document medico- religious beliefs associated with the local phytodiversity of the peoples of Hamirpur. During the survey in the villages of Hamirpur it is found that old age peoples much familiar about the medicinal use of the wild plants. About 22 different wild plants were used by peoples of Hamirpur for the treatment of Kidney stone and Arthritis.